1996
DOI: 10.1111/j.1476-5381.1996.tb15337.x
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric interactions between cyclothiazide and AMPA/kainate receptor antagonists

Abstract: 1 Cyclothiazide blocks a-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptor desensitization and potentiates AMPA receptor gated currents. Interactions between cyclothiazide, and the non-competitive antagonist GYK152466 (GYKI) and competitive antagonist 2,3-dihydroxy-6-nitro-7-sulphamoyl-benzo (F) quinoxaline (NBQX) were studied at native and recombinant AMPA/kainate receptors using whole-cell recording in order to characterize the modulation by cyclothiazide of these two antagonist sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 31 publications
5
19
0
Order By: Relevance
“…Cyclothiazide CTZ selectively blocks desensitization of AMPA receptors, and therefore causes massive potentiation of the responses, both in recombinant and naturally expressed receptors (Partin et al, 1993;Wong & Mayer, 1993;Wilding & Huettner, 1995;Yamada & Turetsky, 1996). Our results show that CTZ concentration-dependently potentiated responses to AMPA of both types of neurones.…”
Section: Kinetic and Rectifying Properties Of Responses Evoked By Rapsupporting
confidence: 57%
See 3 more Smart Citations
“…Cyclothiazide CTZ selectively blocks desensitization of AMPA receptors, and therefore causes massive potentiation of the responses, both in recombinant and naturally expressed receptors (Partin et al, 1993;Wong & Mayer, 1993;Wilding & Huettner, 1995;Yamada & Turetsky, 1996). Our results show that CTZ concentration-dependently potentiated responses to AMPA of both types of neurones.…”
Section: Kinetic and Rectifying Properties Of Responses Evoked By Rapsupporting
confidence: 57%
“…Studies on recombinant receptors show that the action of CTZ is highly dependent on the subunit composition, the splice variants (Sekiguchi et al, 1998) and the editing status (Yamada & Turetsky, 1996;Fleck et al, 1996). Studies on the eect of CTZ on homomerically expressed AMPA receptors showed a wide range of potentiation, with ratios of 102 fold for GluR1 i , 27 fold for GluR2 i , 216 fold for GluR3 i and 16 fold for GluR4 i (Yamada & Turetsky, 1996).…”
Section: Kinetic and Rectifying Properties Of Responses Evoked By Rapmentioning
confidence: 99%
See 2 more Smart Citations
“…The functional effects of the different positive allosteric modulators are complex because multiple partially overlapping binding sites exist (Partin et al, 1996;Yamada and Turetsky, 1996;Lindén et al, 2001;Arai et al, 2002;Sun et al, 2002). The binding sites of compounds that affect desensitization reside within the dimer interface between the ligand binding domains, which supports the interpretation that desensitization involves rearrangement of the dimer interface.…”
Section: A Positive and Negative Allosteric Modulatorsmentioning
confidence: 49%